Chekhov's fiddle: Towards a musical poetics of fiction. Issue 2 (1st October 2019) - Creighton, Alexander
This article explores what it means to listen to Chekhov and how this listening can provide a useful comparative framework for the study of time in short fiction. Since the tune of Chekhov's stories lies partly in their strategic silences, we must attend as much to the unsaid, the musical rests, as to what is told. To theorize the meaningful relations that exist in and between a story's silences and its words, I analyse two of Chekhov's stories – 'Easter Night' and 'The Bishop' – with respect to two key terms: melodic setting and harmonic characterization. These terms refer to phenomena that run counter to our assumptions regarding character and setting by asserting that the movement we associate with the former and the stasis we associate with the latter are reductive. In music, movement and stasis are not always clear-cut terms; harmony and melody are interdependent and influence one another. Even in a symphonic form like the sonata, built around development, stasis plays a role; even in a song that dwells in the description of one mood or conflict, there is development and change. The language of music accommodates the possibility of several independent variables moving simultaneously through time, which, as Chudakov and Woolf notice of Chekhov's work, is part of what makes even the shortest of his stories so profound.